Le commerce régional et international au xe siècle en Syrie : d'après le trésor monétaire de Buseyra et d'autres trésors de l'époque - Chomari, Alaa Aldin Salman al- (Archaeopress Archaeology, 2020)
This volume presents a study of the treasure of Buseyra, which is preserved in the museum of Deir az-Zour in Syria. These coins offer precious information, not only about a large number of mints but also about the periods and quantities of minting activity in the region